Adaptation of the Four Levels of Test Maturity Model Integration with Agile and Risk-Based Test Techniques - Unudulmaz, Ahmet; Cingiz, Mustafa Ozgur; Kalipsiz, Oya (MDPI, 2022)
Many projects that progress with failure, processes managed erroneously, failure to deliver products and projects on time, excessive increases taking place in costs, and an inability to analyze customer requests correctly pave the way for the use of agile processes in software development methods and cause the importance of test processes to increase day by day. In particular, the inability to properly handle testing processes and risks with time and cost pressures, the differentiation of software development methods between projects, the failure to integrate risk management, and risk analysis studies, conducted within a company/institution, with software development methods also complicates this situation. It is recommended to use agile process methods and test maturity model integration (TMMI), with risk-based testing techniques and user scenario testing techniques, to eliminate such problems. In this study, agile process transformation of a company, operating in factory automation systems in the field of industry, was followed for two and a half years. This study has been prepared to close the gap in the literature on the integration of TMMI level 2, TMMI level 3, and TMMI level 4 with SAFE methodology and agile processes. Our research has been conducted upon the use of all TMMI level sub-steps with both agile process practices and some test practices (risk-based testing techniques, user scenario testing techniques). TMMI coverage percentages have been determined as 92.85% based on TMMI level 2, 92.9% based on TMMI level 3, and 100% based on TMMI level 4. In addition, agile process adaptation metrics and their measurements between project versions will be shown, and their contribution to quality will be mentioned.
Keywords: TMMI; agile; SAFE; testing techniques; risk-based tests; test metrics; quality; quality management; TMMI level 2; TMMI level 3; TMMI level 4; Computer Science; Engineering; Physics